Konfrontasi Indonesia-Malaysia Tahun 1963-1966 (Dampak Terhadap Perekonomian Masyarakat Tanjung Balai Karimun) - Imantri Perdana; Ridwan Melay; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The economy is very important for life, especially the life of the state. Before the confrontation economy is quite "passionate", the condition is supported by the use of a dollar as trade of exchange. Riau Islands at that time earned the nickname "Heaven of Dollar" (Surga Dollar). the outbreak of confrontation between Malaysia and Indonesia due in 1961 on the wishes Federation of Malaya was known as “Persekutuan Tanah Melayu” (PTM). wishes combines Brunei, Sabah and Sarawak into the Federation of Malaysia, which is not in accordance with the Agreement of Manila (Manila Accord) and the President considers the establishment of the Federation of Malaysia at that time known as the "British Puppets" is colonialism and imperialism in a new form, in 1963 the United Nations (UN) to lift Malaysia as a non-permanent member of the UN council it also makes the relationship between the two countries became hostile, then take economic measures in the context of confrontation contained in various rules, as a concrete step the government to take decisive action in the monetary field which prohibits the use of exchange rates Dollar Singapore and Malaysia in the Riau Islands which entered into force on October 15, 1963 replaced the currency of Riau Islands Rupiah “Kepulauan Riau Rupiah” (KRRP). The purpose of this study was to determine the factors that lead to confrontation so as to make the economic situation is very difficult, how the economic changes of society at the time of the confrontation and the impact at the time, the situation of government policy in tackling confrontations that have an impact on the economy and the role of the World international or International Organization in addressing the confrontation that occurred between Indonesia and Malaysia, especially in Tanjung Balai Karimun. The method used in this research is qualitative descriptive method. The research location in Tanjung Balai Karimun. When the study began seminar starting from the proposal to the thesis examination. Data collection techniques from sources of books, interviews and the relevant documents. The results showed that the confrontation impact for both countries Indonesia Malaysia, especially the economic problems that occurred in the community of Tanjung Balai Karimun.Keywords: Confrontation, Economics, Tanjung Balai Karimun